A strategic development mechanism to improve the competitiveness and sustainability of metallurgical enterprises - O. A. Velikaya (Вестник университета)
In recent years, in the process of technological sovereignty formation, increasing competitiveness and formation of conditions for the effective development of industrial metallurgical enterprises cause a lot of discussions, the essence of which is reduced to discussing the sanctions imposed on Russian industrial enterprises, affecting the raw materials and components supply, so the research topic is relevant to the domestic industry. The increase of competitive advantages contributes to the development of the national economy of industrial metallurgical enterprises, as their products are used in many industries of the real sector of the economy. The article is aimed at assessing the current level of the strategic development mechanism and increasing competitive advantages and sustainability of the metallurgical industry with effective optimization of supplies’ financial costs based on systematization and forecasting. The carried out study of the scientists’ materials, who worked on the problem and investigated these issues, has shown that a special role is assigned to the strategic development mechanism evaluation, which contributes to improving competitiveness and sustainable development of metallurgical enterprises, as well as the transformation of the regional productive forces and production relations in the metallurgical complex, which at the present stage is entering a new stabilization stage of its development.